278 Helmet utilization and its associated factors among motorcyclists in Ghana. (20th November 2022) - Adjei, Benjamin Noble; Nakua, Emmanuel K; Donkor, Peter; Gyaase, Daniel; Alhassan, Mohammed Muhib; Amissah, John; Enuameh, Yeetey; Mock, Charles
Abstract : Background: The frequency of motorcycle crashes and fatalities in Ghana keep increasing each year, with fatalities from motorcyclists exceeding that of pedestrians in 2020 for the first time. Although wearing a motorcycle helmet reduces the risk and severity of injuries and deaths from these crashes, helmet use remains low. Aim: This study determined the prevalence of helmet use and its associated factors among motorcyclists in Ghana. Methods: Helmet observations were conducted on 3853 motorcycle riders and 1097 pillion riders at 12 randomly selected locations at areas near intersections, roundabouts, and motorcycle bays in the Tamale Metropolis between March and April 2021. Poisson regression model was used to assess the factors associated with helmet use prevalence. Findings: The prevalence of helmet use was 26.7% and 5.7% among riders and pillion riders respectively. The rate of helmet use among riders was higher during the day, weekend and in males but lower among local roads users, younger riders and those with pillion riders. The rate of helmet use among pillion riders was higher in adults but lower in the evening and those with younger riders. Conclusion: In Ghana, motorcycle helmet use is low and strategies are needed to increase it. These strategies can build on the study findings, emphasizing helmet promotion for individuals and scenarios in which there is low helmet use, such as young female riders, pillion riders, evenings and local roads. Learning Outcomes: Helmet use is influenced by time and day of riding, road type, age, and gender of the motorcyclist.